Optimization of Forensic Identification Through 3-dimensional Imaging Analysis of Labial Tooth Surface Using Open-source Software - Arofi Kurniawan; Aspalilah Alias; Mohd Yusmiaidil Putera Mohd Yusof; Anand Marya (Korean Academy of Oral and Maxillofacial Radiology, 2024)
Indexed by WOS/ Scopus